Interpretive and Interpersonal Challenges of Digital Evidence for Public Defenders - Ramirez, Fanny (Human Communication & Technology, 2023)
This study uses an ethnography of a large public defender office in the U.S. to argue that the rise of digital evidence is a communication phenomenon that brings new evidentiary interpretation and interpersonal challenges for public defenders and their low socioeconomic status clients. The study’s theoretical framework draws on communication privacy management theory, context collapse, sensemaking, and sensegiving. Findings holistically show that public defenders now have to engage in collaborative interpretive work with clients to unpack the meaning and context of digital evidence. Content penned by young clients and communications related to domestic violence cases are especially challenging to interpret. Findings also show that access to highly personal data is a double-edged sword for attorney-client interactions in that it can cause feelings of discomfort for attorneys while also holding the potential to humanize clients.